Preventing Corruption in Sports: Russian Experience (Global Journal of Human-Social Science, 2025)
This article explores Russia s comprehensive approach to preventing corruption in sports It outlines key legal mechanisms including mandatory compliance frameworks prosecutorial oversight administrative and criminal sanctions and anti-corruption review of legal acts Drawing on case studies and legislative analysis the paper highlights the Russian Federation s efforts to strengthen institutional integrity and protect the fairness of competition The article contributes to the global discourse on sports governance by presenting the Russian model as an example of holistic anti-corruption policy in practice
Keywords: corruption; sports; compliance; prosecutorial oversight; russian legislation; matchfixing; anti-corruption policy